Farmer participatory assessment of pest management modules for yellow stem borer and leaf folder in summer rice - Nayak, US; Das, A (ORYZA-An International Journal of Rice, 2021)
Rice yellow stem borer, Scirpophaga incertulas (Walker) (Pyralidae: Lepidoptera) is the major pest of rice that causes extensive damage to the crop and its infestation is more severe in summer rice. Field experiment for two consecutive seasons (summer 2014 and 2015) at Bhadrak, Odisha (India) was carried out to assess the relative efficacy of some modules pest management against yellow stem borer and leaf folder in rice. The pest management module comprising of nursery treatment with fipronil 03 G @ 100 g/ cent nursery area at 7 days before transplanting, clipping of leaf tips at transplanting, installation of pheromone traps for mass trapping @ 50/ha, soil application of chlorantraniliprole 0.4 G @ 10 kg/ ha at 30 DAT and foliar spray of indoxacarb 14.5 SC @500 ml/ ha at 60 DAT minimised the stem borer damage substantially (76.40 and 76.15 % reduction of dead heart and white ear head, respectively over control) and contributed to the highest grain yield ( 42.86 % increase over control) with maximum net return (Rs. 19899.05 per hectare) and B :C ratio (1.46). The current pest management module also reduced the infestation level of leaf folder in rice (60.72 % reduction over the untreated control).